Kesalahan Berbahasa pada Teks Prosedural - Cheysa Luthfiah; Indrya Mulyaningsih; Itaristanti Itaristanti (Anufa Ikaprobsi, 2023)
Aspects of language skills that students need to master are writing and reading skills. In writing texts, students must understand spelling, phrases, clauses, sentences, paragraphs, and discourse so that the contents of the text are easily understood properly and correctly. Furthermore, aspects of reading skills also need to be understood by students, if students lack interest in reading, students will make many language mistakes in the order of linguistic rules. Therefore, these two aspects are skills that must be mastered by students. This article focuses on language errors in the text. Thus, this article is important to do in order to find, find, improve, and bring benefits to the assessment of student learning, as well as being a reference for understanding language errors. The study in this article uses descriptive qualitative research, data collection techniques use test, observe, and observe techniques, data validity uses theoretical triangulation, data source triangulation, method triangulation, and expert validation. in the field of spelling students made the most mistakes in the use of capital letters from writing procedural texts of 80 errors. In the prepositional errors, students made many mistakes as many as 7. There were 7 divisions in the classification of syntax field errors and the most students made mistakes in using inappropriate diction. Aspek keterampilan berbahasa yang perlu dikuasai siswa dalam hal ini adalah keterampilan menulis dan membaca. Dalam aspek keterampilan menulis pada sebuah teks, siswa harus mampu memahami tatanan ejaan, frasa, klausa, kalimat, paragraf, serta wacana, supaya apa yang siswa tulis mampu dipahami dengan baik dan benar. Selanjutnya aspek keterampilan membaca pun perlu dipahami oleh siswa, apabila siswa kurang dalam minat baca akan terjadi siswa banyak melakukan kesalahan berbahasa dalam tatanan kaidah kebahasaan. Oleh karena itu, kedua aspek tersebut keterampilan yang harus dikuasai siswa.  Artikel ini memfokuskan terhadap kesalahan berbahasa pada teks. Dengan demikian, artikel ini penting dilakukan guna mencari, menemukan, memperbaiki, dan membawa manfaat terhadap penilaian pembelajaran siswa, serta menjadi acuan pemahaman kesalahan berbahasa. Kajian dalam artikel ini menggunakan penelitian deskriptif kualitatif, teknik pengumpulan data menggunakan teknik tes, simak, dan simak, keabsahan data menggunakan triangulasi teori, triangulasi sumber data, triangulasi metode, dan validasi pakar.  pada bidang ejaan siswa melakukan kesalahan terbanyak ada di penggunaan huruf kapital dari penulisan teks prosedural sebanyak 80 kesalahan. Pada kesalahan preposisi siswa banyak melakukan kesalahan sebanyak 7. Pembagian klasifikasi kesalahan bidang sintaksis ada 7 dan yang paling banyak siswa melakukan kesalahan pada penggunaan diksi yang tidak tepat.